Actors Affecting the Decrease of Maternal Mortality Rates and Problems Related to Birth Services - Rochmayani, Dewi Sari (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
The targeted 102 per 100,000 live births maternal mortality rate (AKI) in Semarang has not been achieved yet. In the era of childbirth insurance program in 2011, AKI reached 119.9 per 100,000. Then, in the era of National Health Insurance (JKN) by Social Security Administrator (BPJS), the AKI in 2004 was 109,2 per 100.000 live births. The study design was qualitative with grounded theory approach. There were 4 research focuses: 1) actors who contribute in labor services; 2) referral delay; 3) Community Health Center (Puskesmas) with basic essential obstetric–neonatal service (Poned); 4) profile of each obstetric services level in Semarang. The results showed that there were 2 groups of actors who contributed to prevention of maternal death. The first group were obstetrics and gynecologists, health surveyors, and professional organizations. The second group were family and society, including husband, mother, in-laws, and public figures. Many maternal death occurred in referral hospitals. There are three types of delay that often occur in Semarang, namely delay in decision-making, delay in accessing health services, and delay in acquiring health services.